2012
DOI: 10.1002/j.1556-6676.2012.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

The Counseling Profession in Russia: Historical Roots, Current Trends, and Future Perspectives

Abstract: Psychology was established in Russia before the Communist era. The social work profession was created in 1991 for a society in turmoil after the collapse of the Soviet Union. In 2011, the counseling profession officially emerged as a branch of social work called social psychological help. Professional counseling associations are in the formative stage. Concern about mental health issues, particularly substance abuse, suggests that the counseling profession could continue to grow in Russia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Although Russia remains the largest country in the world by area with a population exceeding 144 million, the proposed study will be the first trial of online CBT-I, which makes it even more important. Due to unique aspects of culture, history, and different psychology traditions, CBT-I remains unknown and unavailable to the majority of Russian patients ( 46 ). Practice shows that general practitioners and medical doctors commonly lack time and knowledge about CBT-I.…”
Section: Introductionmentioning
confidence: 99%
“…Although Russia remains the largest country in the world by area with a population exceeding 144 million, the proposed study will be the first trial of online CBT-I, which makes it even more important. Due to unique aspects of culture, history, and different psychology traditions, CBT-I remains unknown and unavailable to the majority of Russian patients ( 46 ). Practice shows that general practitioners and medical doctors commonly lack time and knowledge about CBT-I.…”
Section: Introductionmentioning
confidence: 99%
“…Abstracts appearing on only one research team member's spreadsheet were reviewed by both research team members to determine whether or not they focused on addiction counseling and/or counselor educator professional development related to addiction counseling. For example, two JCD articles identified with the keywords substance abuse were not included because they focused on the development of the counseling profession in two countries other than the United States and identified substance abuse as a core issue in those countries (Currie, Kuzmina, & Nadyuk, ; Palmer, Palmer, & Payne‐Borden, ). The research team members determined that these articles did not constitute addiction‐related professional development opportunities for counselor educators.…”
Section: Methodsmentioning
confidence: 99%
“…Alcoholism and alcohol abuse/neglect are the two most common reasons for children being placed in the child welfare system in Russia. Two-thirds of the estimated 700,000 social orphans in Russia today are removed from their families for these reasons (Achmatova, 2010; Currie et al, 2012).…”
Section: Services For Russian Survivors Of Gender Violencementioning
confidence: 99%
“…Consuming vodka at family and other social gatherings is typical and the government has restricted the wine and beer industries to promote vodka as the national alcoholic beverage. Russia's vodka sales increased almost 70 percent between 1990 and 2003, and hard liquor consumption in Russia is estimated to be the highest in the world (Currie et al, 2012). A correlation between alcoholism and women is related to child-bearing and child-rearing problems; two-thirds of respondents in one study reported a high rate of drinking among pregnant women (Kristjanson, 2007).…”
Section: Services For Russian Survivors Of Gender Violencementioning
confidence: 99%